AKIBAT WANPRESTASI DAN OVERMACHT MENURUT KUHPERDATA: (ANALISIS PUTUSAN PENGADILAN NEGERI MAMUJU NOMOR 28/PDT.G.S/2019/PN.MAM TAHUN 2019) - Aditya, Febri; Jaitun, Almas; Santoso, Aji; Azzahra, Atiqah Amalya; Oktarina, Vivin Ermia Sarinari Yopan (Universitas Wiralodra, 2025)
An agreement can be implemented well if the parties have fulfilled their respective achievements as agreed without any party being harmed. However, there are times when the agreement is not implemented properly because of a default by one of the parties or the debtor. Default is a term that refers to non-fulfillment of achievements by the debtor. The occurrence of a default results in the loss of the other party (the opponent of the party in default). In Article 1234 of the Civil Code, because there is a loss by another party, the party who has committed the default must bear the consequences of the opposing party's demands, which can be in the form of: cancellation, agreement. cancellation of the agreement accompanied by a claim for compensation, fulfillment of the agreement and fulfillment of the agreement accompanied by a claim for compensation. Meanwhile, overmacht or force majeure is a situation caused by things that are completely unpredictable by the debtor, resulting in non-fulfillment of achievements. In Article 1245 of the Civil Code, if the debtor is unable to fulfill his obligations due to compelling circumstances, the debtor is not required to bear the burden of the loss.